Conducting on-farm animal research : - Amir, Pervaiz (Winrock International Institute For Agricultural Development, 1989)
The objectives of this book are to give animal scientists the elementary tools to do on-farm livestock analysis and to provide ways for on-farm crop researchers to incorporate the animal component into their studies, thereby making it easier to study complex, mixed farming systems in the developing world.